Trends in : a statistical review of publications from 2003 to 2018 focusing on the most-studied genes and document clusters - Ji-Hyeon Kim; Hee-Jo Nam; Hyun-Seok Park (Genomics & Informatics)
Genomics & Informatics (NLM title abbreviation: Genomics Inform) is the official journal of the Korea Genome Organization. Herein, we conduct a statistical analysis of the publications of Genomics & Informatics over the 16 years since its inception, with a particular focus on issues relating to article categories, word clouds, and the most-studied genes, drawing on recent reviews of the use of word frequencies in journal articles. Trends in the studies published in Genomics & Informatics are discussed both individually and collectively.